Oscilloscopes : how to use them, how they work - Hickman, Ian.; ScienceDirect eBooks (Oxford ; Boston : Newnes, 1995)
Oscilloscopes are essential tools for checking circuit operation and diagnosing faults, and an enormous range of models are available. But which is the right one for a particular application? Which features are essential and which not so important? Ian Hickman has the answers. This handy guide to oscilloscopes is essential reading for anyone who has to use a 'scope for their work or hobby: electronics designers, technicians, anyone in industry involved in test and measurement, electronics enthusiasts ... Ian Hickman's review of all the latest types of 'scope currently available will prove especially useful for anyone planning to buy - or even build - an oscilloscope. The science and electronics of how oscilloscopes work is explained in order to enhance the reader's appreciation of how to use their 'scope. The practical use of oscilloscope is explained with clarity and supported with examples, encouraging the reader to think about the application of their oscilloscope and improve their use of this complex instrument. The advance of digital technology makes this timely revision of Ian Hickman's well known book an essential update for electronics professionals and enthusiasts alike. The only fully up-to-date guide to oscilloscopes available A practical guide to getting the most out of an oscilloscope Essential reading for anyone planning to invest in an expensive piece of equipment.
Preface; Introduction; The basic oscilloscope; Advanced real-time oscilloscope; Accessories; Using oscilloscopes; Sampling oscilloscopes; Digital storage oscilloscopes; Oscilloscopes for special purposes; How oscilloscopes work (1): the CRT; How oscilloscopes work (2): circuitry; How oscilloscopes work (3): storage CRTS; Appendix 1: Cathode ray tube phosphor data; Appendix 2: Oscilloscope manufacturers and suppliers; Index.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Oscilloscopes; Oscilloscopes; Electronic books